2010
DOI: 10.1590/s1679-45082010ao1469
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced ventricular arrhythmias: analysis of predictive factors in a population with sleep disorders

Abstract: Objective: To assess the prevalence of ventricular arrhythmias induced by exercise in a population with sleep disorders and to analyze the triggering factors. Methods: Patients were consecutively selected from the database of the Sleep Clinic of Universidade Federal de São Paulo. All subjects were submitted to basal polysomnography, blood sample collection, physical examination, 12-lead ECG, spirometry, cardiorespiratory exercise study on a treadmill, and echocardiogram. The Control Group was matched for age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…For instance, some respiratory diseases that involve chronic, transitory, or intermittent hypoxia induce the process of fibrosis in cardiac tissue, and increase the occurrence of cardiac arrhythmias. Studies in patients with chronic obstructive pulmonary disease (COPD), obstructive sleep apnea (OSA), and with cystic fibrosis (CF) have shown that low oxygen saturation during exercise may predispose them to cardiac ventricular arrhythmias (Cheong et al, 1990 ; Ruf and Hebestreit, 2009 ; Cintra et al, 2010 ). Cardiac arrhythmia has been also reported in patients with sleep apnea syndrome (SAS) (Guilleminault et al, 1983 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some respiratory diseases that involve chronic, transitory, or intermittent hypoxia induce the process of fibrosis in cardiac tissue, and increase the occurrence of cardiac arrhythmias. Studies in patients with chronic obstructive pulmonary disease (COPD), obstructive sleep apnea (OSA), and with cystic fibrosis (CF) have shown that low oxygen saturation during exercise may predispose them to cardiac ventricular arrhythmias (Cheong et al, 1990 ; Ruf and Hebestreit, 2009 ; Cintra et al, 2010 ). Cardiac arrhythmia has been also reported in patients with sleep apnea syndrome (SAS) (Guilleminault et al, 1983 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some experimental studies have identified the potential association between desaturations and the occurrence of ventricular arrhythmias. However, the underlying mechanism was still unclear [ 28 ]. Patients with respiratory failure were found to be at higher risk of LTA.…”
Section: Discussionmentioning
confidence: 99%